Ipomoea fulvicaulis (Convolvulaceae), a new record for India - Kattee , A. V.; Dalavi, J. V.; Patil , C. R.; Shimpale, V. B. (Rheedea, 2019)
Ipomoea fulvicaulis (Hochst. ex Choisy) Boiss. ex Hallier f. (Convolvulaceae), recently collected from Nandi hills of Karnataka state, is reported here as a new record for the flora of India. A detailed taxonomic account, including description, illustrations and photographs are provided to facilitate easy identification.